1995
DOI: 10.1136/hrt.74.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Dual chamber pacing: how many patients remain in DDD mode over the long term?

Abstract: With careful use of programming facilities and appropriate secondary intervention, most patients with dual chamber pacemakers can be maintained successfully in DDD or an alternative atrial pacing mode until elective replacement, although atrial arrhythmia remains a significant problem. There are no good reasons, other than cost, for not using dual chamber pacing routinely as suggested by recent guidelines and this policy can be achieved successfully in a district general hospital pacing centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 20 publications
4
16
1
Order By: Relevance
“…Our percentage of surgery, including the cases refractory to reprogramming, was much lower than that reported by Gross et al 10 and Ibrahim et al 23 , whose values were 4 and 9.6%, respectively.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Our percentage of surgery, including the cases refractory to reprogramming, was much lower than that reported by Gross et al 10 and Ibrahim et al 23 , whose values were 4 and 9.6%, respectively.…”
Section: Discussioncontrasting
confidence: 51%
“…Detollenaere et al 22 have shown that the incidence of these arrhythmias (12%) does not correlate with mortality. Ibrahim et al 23 have observed that in the presence of sick sinus syndrome, the risk of pacemaker patients for developing atrial fibrillation is 1.5 times higher than that of those with disorders in atrioventricular conduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Former non-randomized studies implied that singlelead VDD pacing might reduce the incidence of atrial fibrillation in patients paced for isolated atrioventricular block [13,14,19,20] . Our data do not support this hypothesis, showing equivalent incidences of atrial fibrillation in prospective comparisons of VDD and DDD devices.…”
Section: Costs Of Complicationsmentioning
confidence: 99%
“…Previous analyses of DDD (dual-chamber pacing and sensing with inhibition and tracking) pacing mode survival have reported that after 2.5-3.4 years, a total of 4-18% of patients receiving a DDD pacemaker are downgraded to VVI pacing, most often due to atrial fibrillation (50-75%) or atrial lead failure (25-35%). [17][18][19][20] Interestingly, none of our dual-chamber pacemaker subjects were recorded atrial fibrillation and none of atrial lead measurement on follow up indicated an atrial lead failure. Our result showed an early pacemaker downgraded compared to other studies.…”
Section: Discussionmentioning
confidence: 99%